2022
DOI: 10.1039/d2cy01638a
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of Ni(CO)4 contaminant during IR analyses using a metal-containing reaction cell

Abstract: The formation of ppm levels of volatile Ni(CO)4 occured in the presence of 1 kPa CO over a worn commercial cell used for diffuse reflectance FT-IR, but not on a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Our DFT investigations found that CO adsorbed over CeO 2 does indeed have prominent peaks at 2173, 2152, and 2132 cm –1 over reduced CeO 2 (111), CeO 2 (111), and CeO 2 (211), respectively, as shown in Figure r. A peak at a lower wavenumber of about 2036 cm –1 could be assigned to impurities as also reported in the literature on a Au/SiO 2 catalyst. ,, In the DRIFTS spectra measured over an inert CaF 2 reference, two very weak CO vibrational frequencies at 2172 and 2116 cm –1 were observed, as shown in Figure S39b. Our DFT calculations of the CO vibrational frequency of Ni­(CO) 4 adsorbed over the CeO 2 (111) facet reveals that the most intense IR peak is located at 2035.1 cm –1 (Figure S39c).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Our DFT investigations found that CO adsorbed over CeO 2 does indeed have prominent peaks at 2173, 2152, and 2132 cm –1 over reduced CeO 2 (111), CeO 2 (111), and CeO 2 (211), respectively, as shown in Figure r. A peak at a lower wavenumber of about 2036 cm –1 could be assigned to impurities as also reported in the literature on a Au/SiO 2 catalyst. ,, In the DRIFTS spectra measured over an inert CaF 2 reference, two very weak CO vibrational frequencies at 2172 and 2116 cm –1 were observed, as shown in Figure S39b. Our DFT calculations of the CO vibrational frequency of Ni­(CO) 4 adsorbed over the CeO 2 (111) facet reveals that the most intense IR peak is located at 2035.1 cm –1 (Figure S39c).…”
Section: Resultssupporting
confidence: 79%
“…A peak at a lower wavenumber of about 2036 cm −1 could be assigned to impurities as also reported in the literature on a Au/SiO 2 catalyst. 76,80,81 In the DRIFTS spectra measured over an inert CaF 2 reference, two very weak CO vibrational frequencies at A more detailed experimental investigation is currently planned.…”
Section: In-situ Xas and Drifts Experimentsmentioning
confidence: 99%